Exploitation Againstwoman in the Novel the Woman Crying to the Black Moon By Dian Purnomo: A Study of Radical Feminism - Baiq Iling Kiranawati; Nurhadi (Britain International for Academic Research (BIAR) Publisher, 2023)
The theme of women is often raised in literary works. Women often experience exploitation from all sides. The research is entitled